Genome-wide selection and introgression of Chinese rice varieties during breeding - Ge, Jinyue; Wang, Junrui; Pang, Hongbo; Li, Fei; Lou, Danjing; Fan, Weiya; Liu, Ziran; Li, Jiaqi; Li, Danting; Nong, Baoxuan; Zhang, Zongqiong; Wang, Yanyan; et al. (Elsevier, 2022)
China is the largest rice-producing country, but the genomic landscape of rice diversity has not yet been clarified. In this study, we re-sequence 1070 rice varieties collected from China (400) and other regions in Asia (670). Among the six major rice groups (aus, indica-I, indica-II, aromatic, temperate japonica, and tropical japonica), almost all Chinese varieties belong to the indica-II or temperate japonica group. Most Chinese indica varieties belong to indica-II, which consists of two subgroups developed during different phases of rice breeding. The genomic segments underlying the differences between these subgroups span 36.32 Mb. The Chinese japonica rice varieties fall into the temperate japonica group, consisting of two subgroups based on their geographical distribution. The genomic segments underlying the differences between these subgroups span 27.69 Mb. These differentiated segments in the Chinese indica varieties span 45 genes with nonsynonymous mutations that are closely related to variations in plant height and grain width. Fifty-four genes with nonsynonymous mutations are associated with the differences in heading date between the two Chinese japonica subgroups. These findings provide new insights into rice diversity in China that will facilitate the molecular breeding.